2018
DOI: 10.22555/joeed.v5i1.2046
|View full text |Cite
|
Sign up to set email alerts
|

Gender Comparison of Emotional Intelligence of University Students

Abstract: Emotional intelligence is a contributing construct to learning and other personal and career developments. It is a perplex notion involving many conceptions which resulted in various tools

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
4
14
0
3
Order By: Relevance
“…These findings from this study confirmed the outcome of an earlier study by (Fida et al,2018). Both revealed that there was a notable statistical difference between learners from either gender.…”
Section: Statistically Significant Differences Of Emotional Intelligence Of Students According Tosupporting
confidence: 91%
“…These findings from this study confirmed the outcome of an earlier study by (Fida et al,2018). Both revealed that there was a notable statistical difference between learners from either gender.…”
Section: Statistically Significant Differences Of Emotional Intelligence Of Students According Tosupporting
confidence: 91%
“…In order to improve identification of teacher mistreatment, schools and teachers should become aware of the prevalence of mistreatment taking place, in particular as teaching is taking place behind closed doors, and efforts must therefore be made to create systems that identify mistreatment. As a starting point, schools should increase awareness of mistreatment and its implications, and train teachers to identify occurrences of mistreatment [87]. Although most teachers do not take an active part in students' victimizations, as bystanders they have a key role in identifying such occurrences [88].…”
Section: Discussionmentioning
confidence: 99%
“…Some research (e.g. Fida et al, 2018;Harrod and Scheer, 2005;Mandell and Pherwani, 2003;Mayer and Geher, 1996;Schutte et al, 1998;Sutarso et al, 1996) has found that females score higher in EI than their male counterparts. Contrary to the above results, some studies (Kong, 2017;Shi and Wang, 2007) have found higher EI levels in males.…”
Section: Emotional Intelligence and Academic Successmentioning
confidence: 99%